Development of Soft Skills from Out-of-School Experiences in Peru. Learnings from Non-Profit Organizations’ Activities in Public Schools in Lima - Mendoza Egusquiza, Carla Lizette (2021)
This research aimed to examine the enhancement of soft skills in public education in Peru through analysing non-profit organisations’ techniques at the school level. The objectives were (a)To understand how the quality of education in Peruvian public schools assures the development of soft skills, (b)To explore the potential of non-profit organisations in supporting the development of soft skills in public schools. Interviews with three non-profit organisations and a government official, alongside reports, were analysed based on an OECD model. The findings include government initiatives that indirectly develop soft skills, but management issues might lead to teacher-centred rather than student-centred methodologies, deterring skills development. Unfriendly environments characterise vulnerable areas for skills development; non-profits become supportive disruptive spaces to cultivate values, ethics, and skills. The discourse analysis concludes that, despite their small scope, they mainly develop collaboration and task performance skills, impacting career decisions, families and communities. Non-profits employ a playful and concrete methodology that fosters the development of soft skills, but which is difficult to implement in public schools due to a lack of resources and school management. Further research should explore non-profits’ impact on skills development. This study is a pioneer in this field in LATAM.